Cardiac transplant vasculopathy. Issue 1 (July 2017) - Tobis, Jonathan M.
Key Points: Transplant vasculopathy is a form of slowly progressive rejection. The interventional cardiologist plays an important role in maintaining survival of this precious commodity by performing PCI. Everolimus drug eluting stents are highly effective and have relatively low occurrence of in‐stent restenosis, but transplant vasculopathy continues to progress in a diffuse pattern.